IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN FIKIH DI MADRASAH TSANAWIYAH AL-IKHLAS FAJAR BULAN LAMPUNG BARAT - ALICIA, SYIFA; SUSANTI, AGUS; ZULAIKHAH, SITI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This study aims to determine the planning, implementation and evaluation of the independent curriculum in the subject of fiqh at Madrasah Tsanawiyah Al-Ikhlas Fajar Bulan West Lampung. The method used in this study is descriptive qualitative which is used to collect narrative data from primary and secondary sources. The study shows that the planning of the Independent Curriculum in the subject of fiqh reflects the high commitment of the school in providing adaptive and relevant education. Teachers at this school are proactive in adjusting learning methods to student characteristics and subject matter. The role of the deputy head of curriculum is very important in overseeing the implementation of the curriculum. Despite challenges in teacher understanding and limited facilities, Madrasah Tsanawiyah Al-Ikhlas Fajar Bulan West Lampung has taken concrete steps such as teacher training and improving facilities. Through the active involvement of teachers and students, as well as the school's strong commitment to integrating the principles of the Independent Curriculum, this school has succeeded in creating a responsive and innovative learning environment. The implementation of the Independent Curriculum in the subject of fiqh is carried out by adjusting learning to student characteristics and subject matter, and emphasizing independent learning and student collaboration. This is done to create education that is relevant and adaptive to the needs of students in an era that is constantly changing. Evaluation of the implementation of the Independent Curriculum in the subject of fiqh at Madrasah Tsanawiyah Al-Ikhlas Fajar Bulan Lampung Barat uses a holistic approach that includes cognitive aspects, skills, character, and student satisfaction. This evaluation is carried out through diagnostic, formative, and summative assessments to monitor student understanding and development. In addition, the evaluation also includes measuring practical skills and assessing student character in accordance with the principles of the Independent Curriculum. ABSTRAKPenelitian ini bertujuan untuk mengetahui perencanaan, pelaksanaan dan evaluasi kurikukulum merdeka pada mata pelajaran fikih di Madrasah Tsanawiyah Al-Ikhlas Fajar Bulan Lampung Barat. Metode yang digunakan pada penelitian ini yaitu deskriptif kualitatif yang digunakan untuk mengumpulkan data yang bersifat naratif dari sumber primer dan sekunder. Penelitian menunjukkan bahwa perencanaan Kurikulum Merdeka pada mata pelajaran fikih mencerminkan komitmen yang tinggi dari sekolah dalam menyediakan pendidikan yang adaptif dan relevan. Guru-guru di sekolah ini proaktif dalam menyesuaikan metode pembelajaran dengan karakteristik siswa dan materi pelajaran. Peran wakil kepala kurikulum sangat penting dalam mengawasi implementasi kurikulum. Meskipun terdapat tantangan dalam pemahaman guru dan keterbatasan fasilitas, Madrasah Tsanawiyah Al-Ikhlas Fajar Bulan Lampung Barat telah mengambil langkah-langkah konkret seperti pelatihan guru dan peningkatan fasilitas. Melalui keterlibatan aktif guru dan siswa, serta komitmen sekolah yang kuat dalam mengintegrasikan prinsip-prinsip Kurikulum Merdeka, sekolah ini berhasil menciptakan lingkungan pembelajaran yang responsif dan inovatif. Pelaksanaan Kurikulum Merdeka pada mata pelajaran fikih dilakukan dengan menyesuaikan pembelajaran terhadap karakteristik siswa dan materi pelajaran, serta menekankan pembelajaran mandiri dan kolaborasi siswa. Hal ini dilakukan untuk menciptakan pendidikan yang relevan dan adaptif terhadap kebutuhan siswa di era yang terus berubah. Evaluasi implementasi Kurikulum Merdeka pada mata pelajaran fikih di Madrasah Tsanawiyah Al-Ikhlas Fajar Bulan Lampung Barat menggunakan pendekatan holistik yang meliputi aspek kognitif, keterampilan, karakter, dan kepuasan siswa. Evaluasi ini dilakukan melalui asesmen diagnostik, formatif, dan sumatif untuk memantau pemahaman dan perkembangan siswa. Selain itu, evaluasi juga mencakup pengukuran keterampilan praktik dan penilaian karakter siswa sesuai dengan prinsip-prinsip Kurikulum Merdeka.